Factors affecting shale microscopic pore structure variation during interaction with supercritical CO2. Issue 38 (May 2020) - Dai, Xuguang; Wang, Meng; Wei, Chongtao; Zhang, Junjian; Wang, Xiaoqi; Zou, Mingjun
Highlights: Pore volume, surface area and average pore size of shale were obtained during interaction with ScCO2 . MPS variation influenced by TOC before and after ScCO2 treatment was investigated. MPS variation under different temperature and pressure was studied. MAQ model was used to characterize the adsorption capacity of shale. Abstract: Substantial physiochemical changes occur during the interaction between supercritical carbon dioxide (ScCO2 ) and shale. It is important to clarify the variation and controlling factors of the microscopic pore structure (MPS). Six samples collected from Longmaxi Formation with various material compositions were treated with ScCO2 . X-ray diffraction (XRD), scanning electron microscope (SEM), gas adsorption, and the maximum adsorption quantity ( MAQ ) model were employed to determine parameters before and after ScCO2 treatment. XRD data document feldspar, carbonate, and clay decrease after ScCO2 treatment. Specifically, the dissolution of clay and carbonate increases the micropore volume and mesopore specific surface area (meso-SSA), respectively. From gas adsorption results, two types based on the difference in total organic content (TOC) are identified, i.e. an accelerating improvement (samples with a TOC less than 3.00 %) and a moderating improvement (samples with a TOC greater than 3.00 %). Data from gas adsorption also support increased MPS parameters with pressure, indicating the variation can be classified into three discernible phases, i.e. a negligible variation at low-pressure, a swift increase at medium-pressure, and a sharp increase at high-pressure. Temperature, however, has a limited improvement on the MPS. These findings are likely to impact the MPS variation in the process of CO2 -enhanced shale gas recovery (CO2 -EGR).